Produksi Abon Berbahan Dasar Ikan sebagai Inovasi Produk Pangan - Kevin Gustian Yulius; Theodosia C. Nathalia (Jurnal Pariwisata Indonesia, 2023)
Fish is one of the many fishery products produced in Indonesia and is a source of animal protein which is consumed by many people. This study aims to (1) find out the innovation of fish-based floss products, (2) find out which fish is suitable as a basic ingredient for making fish floss, (3) find out the added value of making fish into fish floss. The method used in this study is descriptive quantitative using organoleptic tests consisting of hedonic quality tests and hedonic tests on panelists. From the results of the organoleptic test, it was found that catfish fish showed the mean value for each color indicator (3.30), aroma (3.47), taste (3.20), and texture (3.33). Furthermore, the results of testing the dory floss showed values for color indicators (2.97), aroma (3.20), taste (3.63), and texture (3.20). Lastly, the Jambal Roti test showed mean values for color (2.90), aroma (3.17), taste (2.90), and texture (3.27). The results of the hedonic test showed that the mean values for catfish floss for each indicator were color (3.67), aroma (3.67), taste (3.33), and texture (3.33). Furthermore, the results of testing the dory floss showed values for color indicators (3.33), aroma (4.00), taste (3.67), and texture (3.33). Lastly, jambal roti testing showed mean values for color (3.00), aroma (3.67), taste (2.67), and texture (3.00). As a result, all floss products in this study were acceptable, but balanced floss catfish and dory products were the most preferred.